2021
DOI: 10.3390/v13122502
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Biology, Recombinant Adenovirus, and Adenovirus Usage in Gene Therapy

Abstract: Gene therapy is currently in the public spotlight. Several gene therapy products, including oncolytic virus (OV), which predominantly replicates in and kills cancer cells, and COVID-19 vaccines have recently been commercialized. Recombinant adenoviruses, including replication-defective adenoviral vector and conditionally replicating adenovirus (CRA; oncolytic adenovirus), have been extensively studied and used in clinical trials for cancer and vaccines. Here, we review the biology of wild-type adenoviruses, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 95 publications
0
42
0
Order By: Relevance
“…Most adenoviruses use the Coxsackie Adenovirus receptor (CAR) to infect cells, but some species (HAdV-B) enter the cell through binding to the complement regulatory protein CD46, which is ubiquitously expressed on many cancer cells [ 20 ]. Studies in animal models and clinical trials have demonstrated efficient infection and replication in lung mesothelioma, lung carcinoma, ovarian epithelial-like tumours, adenosquamous carcinoma, head and neck squamous cell carcinoma, colon carcinoma, colorectal adenocarcinoma, gastric adenocarcinoma, prostate carcinoma, pancreatic adenocarcinoma, melanoma, fibrosarcoma cells, glioblastoma, hepatocarcinoma cells, leukemic monocytes/macrophages [ 21 , 22 ]. Last generation helper-dependent adenovirus vectors (HDAds), also called “gutless” or fully deleted vectors, containing only inverted terminal repeats and the genome pack-aging signal, allow up to 36 kb insertions.…”
Section: Viral Vector Platforms For Cancer Therapymentioning
confidence: 99%
“…Most adenoviruses use the Coxsackie Adenovirus receptor (CAR) to infect cells, but some species (HAdV-B) enter the cell through binding to the complement regulatory protein CD46, which is ubiquitously expressed on many cancer cells [ 20 ]. Studies in animal models and clinical trials have demonstrated efficient infection and replication in lung mesothelioma, lung carcinoma, ovarian epithelial-like tumours, adenosquamous carcinoma, head and neck squamous cell carcinoma, colon carcinoma, colorectal adenocarcinoma, gastric adenocarcinoma, prostate carcinoma, pancreatic adenocarcinoma, melanoma, fibrosarcoma cells, glioblastoma, hepatocarcinoma cells, leukemic monocytes/macrophages [ 21 , 22 ]. Last generation helper-dependent adenovirus vectors (HDAds), also called “gutless” or fully deleted vectors, containing only inverted terminal repeats and the genome pack-aging signal, allow up to 36 kb insertions.…”
Section: Viral Vector Platforms For Cancer Therapymentioning
confidence: 99%
“…Adenovirus (AdV) is a double-stranded DNA without an envelope, containing approximately 26–48 kBP in its genome [ 81 ]. More than 60 human adenoviruses have been identified, with adenovirus serotypes 5 (Ad5) widely used as a gene delivery vector [ 81 ].…”
Section: Biomaterial-mediated Gene Therapy In Cartilage Repairmentioning
confidence: 99%
“…Adenovirus (AdV) is a double-stranded DNA without an envelope, containing approximately 26–48 kBP in its genome [ 81 ]. More than 60 human adenoviruses have been identified, with adenovirus serotypes 5 (Ad5) widely used as a gene delivery vector [ 81 ]. Adenoviruses have low or no toxicity in humans, and high transduction efficiency in both mitotic and non-mitotic cells [ 81 , 82 ].…”
Section: Biomaterial-mediated Gene Therapy In Cartilage Repairmentioning
confidence: 99%
“…The vector is responsible for the delivery of the nucleic acid to the target, avoiding its degradation and systematic adverse effects. The majority of vectors are viral vectors such as adenoviruses ( Zhu et al, 2020 ; Voysey et al, 2021 ; Watanabe et al, 2021 ), retroviruses ( Rastegar et al, 2009 ), lentiviruses ( Maude et al, 2014 ; Sessa et al, 2016 ) or adeno-associated viruses ( Wuh-Liang et al, 2012 ; Keiser et al, 2016 ; Mendell et al, 2017 ; Wang et al, 2018 ). Currently, many scientific groups propose generally safe viral vectors as efficient gene delivery platforms ( Walther and Stein, 2000 ; Bulcha et al, 2021 ; Selvaraj et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%